Violence against women: feminicide, normative evolution and jurisprudence of the Inter-American Court of Human Rights - Gómez-Fontecha, Fidel (2023)
The objective of this article is to briefly review the international normative evolution in the fight against discrimination and violence against women, including the norm as a factor of inequality, as well as the internationally articulated efforts for its eradication; the creation of protection mechanisms in the inter-American system and the development of the main standards of the jurisprudence of the Inter-American Court of Human Rights, concluding with a brief reflection on the situation that Costa Rica is going through this phenomenon.